Existence of Optimal Programs of Accumulation for an Infinite Time Horizon - von Weizsacker, Carl Christian (Review of Economic Studies, 1965)
Journal Article Existence of Optimal Programs of Accumulation for an Infinite Time Horizon Get access Carl Christian von Weizäscker Carl Christian von Weizäscker Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 2, April 1965, Pages 85–104, https://doi.org/10.2307/2296054 Published: 01 April 1965